Manajemen dalam Rantai Layanan Tuberkulosis di Negara Berkembang (Systematic Literature Review) - Yusniar Aviva Nur Yusuf; Andi Susilawati; Fatmawaty Mallapiang (Universitas Pahlawan Tuanku Tambusai, 2026)
Tuberculosis remains a public health problem in developing countries due to the high disease burden, delayed diagnosis, unequal access to services, drug resistance, social stigma, and weak program sustainability. Although various TB control policies and interventions are in place, achievements in prevention, case detection, and treatment have not fully met program targets. This study aims to analyze implementation gaps in the tuberculosis service chain in developing countries, particularly regarding prevention management, case detection, and treatment. The study employs a Systematic Literature Review method using a critical narrative synthesis approach. Articles were searched via Google Scholar, PubMed, NCBI, Elsevier, and Sinta using the keywords “Global Tuberculosis Cases,” “Tuberculosis Case Detection,” “Tuberculosis Control,” and “Tuberculosis Prevention.” Article selection was conducted in accordance with PRISMA. Of the 3,607,463 initial articles, 2,523 were screened based on title and abstract, 1,505 were assessed for full-text eligibility, and 29 met the criteria for analysis. Research findings indicate that TB prevention is still hampered by uneven intervention coverage, poor TB-HIV integration, inconsistent preventive behaviors, and environmental factors. Case detection continues to face obstacles such as delayed diagnosis, low continuity from screening to diagnostic testing, and weak reporting. TB management is still burdened by treatment discontinuation, MDR/XDR-TB, catastrophic costs, stigma, and suboptimal monitoring. These findings underscore that TB control in developing countries requires integrated management that links prevention, screening, diagnosis, treatment, patient support, and surveillance into a single, continuous service chain.